PENGARUH PROFITABILITAS, LIKUIDITAS , GROWTH DAN MEDIA EXPOSURE TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Dan Perusahaan Jasa Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2015) - Hasnia Hasnia; Siti Rofingatun (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2017)
This study aims to determine whether the effects of profitability, liquidity, growth, andmedia exposure to Corporate Social Responsibility Disclosure. This study uses a quantitativeapproach to population studies that firms belonging to the manufacturing and service sectors listedin Indonesia Stock Exchange in 2013, 2014 and 2015. The research proves that the partialprofitability, liquidity and growth has no effect on the disclosure of corporate social responsibility,while media exposure have a significant effect on the disclosure of corporate social responsibility.Simultaneously profitability, liquidity, growth and media exposure together have an effect on thedisclosure of corporate social responsibility.In this study the researchers conducted additional tests are different tests on the disclosure of socialresponsibility, which is to see whether there are differences between manufacturing and servicecompanies related to the disclosure of social responsibility in revealing its social responsibility